Bralni vzori 2 (University of Maribor Press, 2025)
Reading Role Models 2. The scholarly monograph Reading Role Models 2 contains eight chapters divided into three major homogenous entities. The first section presents reading habits, ways of choosing reading material for teachers and librarians, and the reading culture of adults that affects the motivation for reading in children and young adults. The second section presents an analysis of educational study programmes (for pre-school level, generalist primary school teaching, and subject-based primary and secondary school teaching) and what proportion of components of reading literacy various subjects include in order to encourage reading literacy in all areas of learning and teaching. The third section gives examples of two focus groups that were conducted with teachers of various subjects in primary and secondary schools. The publication was created as part of the targeted research project Reading role models: reading habits of professional workers in kindergartens, schools, faculties and general libraries (CRP V5-2361), the aim of which is the study and evaluation of the importance of reading habits with professionals in education and libraries.